spectrophotometric Assay of Metoclopramide Hydrochloride in pharmaceutical preparations via oxidative coupling Reaction with proma zine Hydrochloride and N-Bromosuccinimide - Elham Salih; Intisar Mohamad; Shayma Al-Najafi (College of Education for Pure Sciences, 2006)
Simple, rapid and sensitive spectrophotometric rnethod for the determination of metoclopramide hydrochloride in a bulk sample and in dosage forms is described. The method depends on the oxidative coupling reaction of metoclopramide. HCI with promazine. HCI in the presence of N-bromosuccinimide to form a bluish-green product which absorbs at 600 nm. Beer's law is obeyed in the concentration range 0.4-28.0 pg/ml with good accuracy (average recovery) 100.92% and precision (RSD) is less ihur, 2.0%. The molar absorptivity is t4917 l.mol-'.cm-' with detection and quantification limits 0.11 pg/ml and 0.37 pglml respectively. Common excipients used as additives in pharmaceuticals do not interfere in the proposed rnethod. The method is successfully employed for the detennined of metoclopramide.HCl in pharmaceutical preparations and the results agree favourably with S.D.I. and British pharmacopoeia methods and also with certified values.